Growth model analysis of wild hyacinth macaw (Anodorhynchus hyacinthinus) nestlings based on long-term monitoring in the Brazilian Pantanal - Guedes, Neiva Maria Robaldo; Toledo, Maria Cecília Barbosa; Fontoura, Fernanda Mussi; da Silva, Grace Ferreira; Donatelli, Reginaldo José [UNESP] (Springer Nature, 2022)
Studies on the breeding of vulnerable and endangered bird species are hindered by low numbers of individuals, inaccessible location of nests, unfavourable environmental conditions, and complex behavioural patterns. In addition, intraspecific variation may emerge only following long-term, systematic observations of little-known patterns and processes. Here, data collected over 30 years were used to determine growth model of hyacinth macaw (Anodorhynchus hyacinthinus) chicks in the Pantanal biome of Brazil. During this period, the speed of growth and body mass of chicks varied widely. Four growth models were tested: logistic, Gompertz, Richards, and cubic polynomial. They were fitted using three biometric measurements: body mass, total length, and tail length. The best-fitting growth curves were identified using Akaike’s information criterion. The best models were the cubic polynomial for body mass, Richards for total length, and Gompertz for tail length. We confirmed the occurrence of dwarf individuals, whose body mass, total length, and tail length were 20%, 22%, and 70% smaller, respectively, than in the overall population. The dwarfs remain small in size after having fledged and are easily identified as adults. We discuss the importance of long-term studies to identify windows of opportunity for further research that will help in the conservation of endangered macaw species.